Report on the 18th International Scientific Conference in the Series “Humanistic Ecology” “Contemporary Environmental Dilemmas: Interdisciplinary Approaches” (Bratislava, 26-27 September 2024) - Agnieszka Klimska (Studia Ecologiae et Bioethicae)
The Editorial Team does not provide abstracts for reports.